RELIGIOUS-BASED COMMUNITY AND CONCERN ON MARINE ISSUE: THE PROTESTANT CHURCH OF MALUKU EXPERIENCES - Nancy N. Souisa; Steve G. C. Gaspersz; Fabian N. J. Souisa (International Journal of Education, Information Technology, and Others, 2019)
This article focuses on the roles of religious communities within particular social contexts which concern on environmental sustainability. On the one side, it contains a holistic notion, i.e. interconnection of all living fields and living beings with their milieu. It proves that religion's values ​​to communal practices demonstrate a concern for natural sustainability. On the other side, the dynamic of such interest toward environmental sustainability influences a critical exploration and even transformation of religious values. Among religious communities, in Maluku context, the Protestant Church of Maluku (Gereja Protestan Maluku – GPM) is a Christian community that deliberately and systematically struggles on the problem of environmental sustainability by its religious values ​​(Christianity).